CONVERSATIONAL IMPLICATURE IN SENTILAN SENTILUN TALK SHOW - Lusi Lisnaria Manalu; Lidiman Sahat Martua Sinaga (State University of Medan, 2016)
Talk shows such as Sentilan Sentilun are quite popular in Indonesian television. These talk show are quite interesting to study because they are not only involving many participants, but also requiring the settings in which politeness and implicature needed to be used to keep the communication flows smoothly. This paper is a pragmatic study that aims at investigating conversational implicature that hosts and the guests of Sentilan Sentilun talk show operate within their utterances along with the possible implications that lie behind the implicature. The data are analyzed based on cooperative principle by violating Gricean maxims, that are specifically maxim of quality, quantity and relevance. Findings show that there are 51 utterances containing conversational implicature. The findings show that there are four types of violated maxims that potentially caused conversational implicature. The dominant type is maxim of relation(56.87 %). The reason why it becomes the dominant type is because the host and the guests wanted to create humors in order to flutter someone or certain topics. The hosts and the guests conveyed an implicit meaning when giving statement or opinion or information and answering the question in their discussion based on the truth condition or facts in the talk show.